Region of Origin in the United States Affects Price Premiums Associated with Value-Added Health Protocols of Beef Calf Lots Sold Through Summer Video Auctions from 2010 Through 2018 - M. J. Smith; E. D. McCabe; M. E. King; K. E. Fike; G. M. Rogers; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:The objective was to evaluate the effects of value-added calf health protocols within various regions of the United States on the sale price of beef calf lots sold via summer video auction. Study Description:Information describing lot factors was obtained through a livestock video auction service (Superior Livestock Auction, Fort Worth, TX). Descriptive characteristics were available over nine years (2010-2018) representing 43,242 lots of beef calves. Data were evaluated to investigate participation in various health programs across regions. A multiple regression model was developed for each region to determine the value associated with health protocols throughout regions of the United States. The Bottom Line:While variation in the sale price of beef calves across regions suggests evident differences in the recognized value by buyers, results indicate the value associated with the vaccination and management of calves with potentially larger transportation distances from origin to delivery.
Keywords: video auction; value-added health protocol; beef calves